Case Report on Ewing’s Sarcoma - A Defaulter Stepped into Metastasis - Sabu, Neetha; Thomas, Blessy Rachel; TJ, Catherin; Baby, Neenu; ES, Lekshmi; James, Apollo; Sivakumar, T (Indian Journal of Pharmacy Practice)
Ewing’s sarcoma is a very rare type of malignant tumour that grows in bones or the soft tissue around the bones, such as cartilage or the nerves. It usually affects people from the ages of 10 to 20 and has a high rate of being cured. Children with Ewing’s sarcoma that hasn’t spread have cure rates as high as 80%. Even if the treatment works, patients still need to follow up for many years. Ewing’s sarcoma can return even a decade after the diagnosis. This is a case of 9-year-old male patient with a known case of Ewing’s sarcoma diagnosed 3 years back. He was treated according to National Comprehensive Cancer Network recommendations for Ewing’s sarcoma and later he defaulted for 1 year. Now he is at the stage of metastasis of Ewing’s sarcoma. The study points out that there is an utmost importance of regular follow ups and therapeutic value of completing the treatment.
Keywords: Ewing’s sarcoma; Defaulter; Metastasis; Chemotherapy